Presentasi Perempuan dalam Perspektif Ekofeminisme pada Film Marlina Si Pembunuh dalam Empat Babak - Resky Apriliani Basnapal; Roro Retno Wulan (Jurnal Komunikasi, 2019)
This study aims to describe the women depicted in the film "Marlina, the murderer in four rounds". The film discusses Marlina's struggle in the form of domination carried out by robbers. Marlina here is analogized as a natural management woman who is ready to fight against the patriarchal system. This research is based on the study of ecofeminism which is divided into three perspectives that will become the eyes of researchers, namely knowledge, intuition, and spiritual. Using qualitative research methods with Roland Barthes's semiotic approach. The data sources used are primary data, and secondary data through literature studies such as journals, theses, papers, books, and so on. The results of the study show that Marlina as a natural manager is analogous to no-man's land, trade products, producers / births can be mastered, oppressed, or exploited. This cause natural imbalances such as disasters that Marlina represents for Mark's death. Keyword : ecofeminism, women, nature, film, roland barthes’s semiotics